VERTICAL LAND UTILIZATION BY MEANS OF STOREY HOUSING DEVELOPMENT IN URBAN ARE - Sukanti, Arie (Indonesia Law Review, 2011)
Many international covenants and constitutions have recognized housing and shelter needs as one of many human right aspects. This paper intends to clarify the particular issues relating to paragraph 19 of the United Nations Millennium Declaration, on resolving city slum problems. The Declaration has also embedded initiative to achieve a significant improvement in the lives of at least 100 million slum dwellers as proposed in the “Cities without Slums” by 2020. In the local perspectives, based on existing regulations analysis, the Special Region (DKI) of Jakarta has many problems on forthcoming implementation. Vertical land utilization model by way of storey houses development becomes an alternative to settle the demographic and housing problems. More legal research needs to be conducted to find the best effective national policy in the future. Urban land use, proposed as starting points, will be able to explore how to provide and undertake vertical land utilization and city planning to resolve city slums problems by providing both housing needs and city attractiveness as an integrated planning.